1997
DOI: 10.1902/jop.1997.68.12.1151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irradiation of an Erbium: YAG Laser on Root Surfaces

Abstract: The application of erbium:yag laser (Er:YAG) irradiation has been investigated for periodontal therapy. The purpose of this study was to evaluate the effects of Er: YAG laser irradiation on root surfaces using a scanning electron microscope (SEM) and to determine the laser's ability to remove lipopolysaccharides (LPS). Infrared spectrophotometry was used to investigate the effects of the laser on LPS applied to root dentin pellets. Premolare extracted for orthodontic reasons were prepared for this study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(126 citation statements)
references
References 38 publications
4
114
0
8
Order By: Relevance
“…The application of dental laser is increasingly popular in the endodontic field, and many studies have been demonstrated for their use [21]. Most reports have indicated that laser irradiation is useful for bacterial reduction [22].…”
Section: Discussionmentioning
confidence: 99%
“…The application of dental laser is increasingly popular in the endodontic field, and many studies have been demonstrated for their use [21]. Most reports have indicated that laser irradiation is useful for bacterial reduction [22].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that Er:YAG laser could remove 83% of lipopolysaccharide from the root surface, suggesting Er:YAG laser as a useful root conditioner [81]. Laser application on root surface has a significant effect on fibroblast attachment.…”
Section: Hyaluronic Acid (Ha) Lasersmentioning
confidence: 93%
“…Lasers have been studied for their effect on root surface [76][77][78][79][80][81][82] as well as for their effects on the behaviour on periodontal ligament cells [83][84][85]. Although, laser therapy has been widely studied in periodontics for pocket debridement, wound healing and in various surgical approaches but there is insufficient data available regarding its efficacy in root surface biomodification when compared with other traditionally used root surface conditioners.…”
Section: Hyaluronic Acid (Ha) Lasersmentioning
confidence: 99%
“…Ando et al (1996) observed a bactericidal effect against P. gingivalis and A. actinomycetemcomitans even at low energy level (Ando et al 1996). Moreover, the wavelength of Er:YAG laser correspond to the peak of absorbance of bacterial lipopolysaccharide, so that the Er:YAG laser can effectively and rapidly remove most of the lipopolysaccharide that coat the teeth (Yamaguchi et al,1997).…”
Section: Periodontal Applications Of Er:yag Lasermentioning
confidence: 99%